Reproductive development of common buckwheat (Fagopyrum esculentum Moench) and its wild relatives provides insights into their evolutionary biology - Sokoloff, Dmitry D.; Malyshkina, Raisa A.; Remizowa, Margarita V.; Rudall, Paula J.; Fomichev, Constantin I.; Fesenko, Aleksey N.; Fesenko, Ivan N.; Logacheva, Maria D. (Frontiers in Plant Science, 2023)
Introduction Understanding the complex inflorescence architecture and developmental morphology of common buckwheat (Fagopyrum esculentum) is crucial for crop yield. However, most published descriptions of early flower and inflorescence development in Polygonaceae are based on light microscopy and often documented by line drawings. In Fagopyrum and many other Polygonaceae, an important inflorescence module is the thyrse, in which the primary axis never terminates in a flower and lateral cymes (monochasia) produce successively developing flowers of several orders. Each flower of a cyme is enclosed together with the next-order flower by a bilobed sheathing bract-like structure of controversial morphological nature. Methods We explored patterns of flower structure and arrangement in buckwheat and its wild relatives, using comparative morphology, scanning electron microscopy and X-ray microtomography. Results Our data support interpretation of the sheathing bract as two congenitally fused phyllomes (prophylls), one of which subtends a next-order flower. In tepal-like bract, a homeotic mutant of F. esculentum, the bilobed sheathing bract-like organ acquires tepal-like features and is sometimes replaced by two distinct phyllomes. Wild representatives of F. esculentum (ssp. ancestrale) and most cultivars of common buckwheat possess an indeterminate growth type with lateral thyrses produced successively on the primary inflorescence axis until cessation of growth. In contrast, determinate cultivars of F. esculentum develop a terminal thyrse after producing lateral thyrses. In contrast to F. esculentum, the occurrence of a terminal thyrse does not guarantee a determinate growth pattern in F. tataricum. The number of lateral thyrses produced before the terminal thyrse on the main axis of F. tataricum varies from zero to c. 19. Discussion The nine stages of early flower development formally recognized here and our outline of basic terminology will facilitate more standardized and readily comparable descriptions in subsequent research on buckwheat biology. Non-trivial relative arrangements of tepals and bracteoles in Fagopyrum and some other Polygonaceae require investigation using refined approaches to mathematical modelling of flower development. Our data on inflorescence morphology and development suggest contrasting evolutionary patterns in the two main cultivated species of buckwheat, F. esculentum and F. tataricum. The genus Fagopyrum offers an excellent opportunity for evo-devo studies related to inflorescence architecture.